Pendidikan Jasmani Berkelanjutan dalam Mewujudkan School Well-Being - Septiani, Erin; Vega, Shofie Amalia; Meisya, Dea; Juliantine, Tite (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This research aims to present a systematic literature review to identify, analyze, and synthesize research results on the contribution of sustainable Physical Education to school welfare. The study involved a variety of physical education interventions, including structured physical activity, teacher training, and innovative pedagogical approaches, to improve student engagement, mental health, social skills, and physical fitness. The study results show that a sustainably designed Physical Education program supports enhanced physical health and improves students' cognitive, social, and emotional development. The continued implementation of Physical Education in schools has proven effective in creating a more inclusive and positive learning environment. However, the lack of facilities and teacher training is still an obstacle to implementing the program. The conclusion is that this study provides insight for educators and policymakers to develop more effective strategies to holistically integrate the concept of sustainable Physical Education to improve school welfare. Keywords: Continuing Physical Education, School Wellbeing, Physical Health, Mental Health, Inclusivity.